PENGARUH EFEKTIVITAS BEASISWA BIDIKMISI TERHADAP PENINGKATAN HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERISITAS RIAU - Ayuningrum, Larasati; Suarman, Suarman; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research aims to determine the influence of the bidikmisi scholarship effectiveness on the enchanment learning outcomes of students of Economic Education Studies Program FKIP Univerisity of Riau. The population in this study are students of the recipient of the scholarship Education Program of Economics from 2015 to 2017 as many as 53 students and in this research using a census sample technique in which all populations are made samples which is 53 students. Data measurement using questionnaires and documentation. Data is collected using questionnaires on the effectiveness of the bidikmisi scholarship distributed to respondents and requesting the IP list of students during their studies to see the increase in student outcomes. Data analysis uses simple linear regression test data analysis. The results showed the effectiveness of bidikmisi scholarships significant effect on the improvement of student learning outcomes Program of Economic Education FKIP Univerisitas Riau. Judging by the calculation of R2 (R Square) obtained a value of. The meaning is that contributions contribute to the effectiveness of the scholarship to improve learning outcomes by 37.3%, while the remaining of 62.7% is influenced by other factors that are not researched in this study.Key Words: Effectiveness, Bidikmisi Scholarship, Enhancement Learning Outcomes